2019
DOI: 10.1590/fst.27917
|View full text |Cite
|
Sign up to set email alerts
|

Protein beverages containing anthocyanins of jabuticaba

Abstract: The objective of this study was to develop, characterize and evaluate the stability of whey protein beverages containing anthocyanins from jabuticaba skins. Beverage formulations containing 0.5% (F1), 2.0% (F2), 4.0% (F3) and 6.0% (F4) of whey proteins and 2.0 mL of the concentrated phenolic extract from jabuticaba skins were developed. Physicochemical parameters (pH, acidity, total soluble solids, protein content, viscosity, color), antioxidant capacity, total anthocyanins and total phenols of the beverages w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Anthocyanins were the group of flavonoids identified in wines [ 115 , 118 , 119 ], liqueurs [ 117 ] and other alcoholic beverages [ 109 ], mainly by their glycosidic derivatives. Anthocyanins were also quantified in protein drinks (average of 1.6 mg/100 g) and in isotonic drinks (average of 2.61 mg of cyanidin-3-glucoside in 100 mL) [ 113 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anthocyanins were the group of flavonoids identified in wines [ 115 , 118 , 119 ], liqueurs [ 117 ] and other alcoholic beverages [ 109 ], mainly by their glycosidic derivatives. Anthocyanins were also quantified in protein drinks (average of 1.6 mg/100 g) and in isotonic drinks (average of 2.61 mg of cyanidin-3-glucoside in 100 mL) [ 113 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that preheated WPI at 100 °C could effectively improve the color stability of RAE in the beverage model system [ 126 ]. In another study, the total anthocyanins and physicochemical properties of the WP (4.0%) beverage formula did not show significant changes with storage time [ 146 ]. WP drinks containing anthocyanins from Robinia pseudoacacia peel have good stability and great market potential.…”
Section: Application Of the Interaction Between Anthocyanins And Prot...mentioning
confidence: 99%
“…Zhu et al [207] used surface hydrophobicity properties to form nanocomplexes consisting of whey proteins and fucoxanthin [207]. Prevention of oxidative degradation of carotenoids or other phenolic compounds has been reported, after the inclusion of the aforementioned compounds into WPI emulsions [208,209,210]. Moreover, increased bioavailability of astaxanthin in Caco-2cell models on whey protein nanodispersion was recently demonstrated [211].…”
Section: Whey Proteins: Research Insights and Trendsmentioning
confidence: 99%